2014
DOI: 10.1055/s-0034-1384546
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Ischemic Preconditioning does not Improve Performance during Self-Paced Exercise

Abstract: Muscle ischemic preconditioning (IP) has been found to improve exercise performance in laboratory tests. This investigation aims at verifying whether performance is improved by IP during self-paced exercise (SPE) in the field. 11 well-trained male runners performed 3 randomly assigned 5 000 m self-paced running tests on an outdoor track. One was the reference (RT) test, while the others were performed following muscle IP (IPT) and a control sham test (ST). Average speeds were measured during each test. Mean va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 32 publications
5
38
0
Order By: Relevance
“…IPC had no beneficial effects on the mean V ・ O2, V ・ E, and HR during a 5 km running time trial 22) , the submaximal V ・ O2 during maximal incremental leg cycling 13,14) , or during leg cycling at an exercise intensity of 90% V ・ O2peak at the gas exchange threshold 12) . However, IPC decreased LA at the submaximal running speed compared to SHAM 21) .…”
Section: Physiological Responses At Submaximal Work Loadmentioning
confidence: 88%
See 4 more Smart Citations
“…IPC had no beneficial effects on the mean V ・ O2, V ・ E, and HR during a 5 km running time trial 22) , the submaximal V ・ O2 during maximal incremental leg cycling 13,14) , or during leg cycling at an exercise intensity of 90% V ・ O2peak at the gas exchange threshold 12) . However, IPC decreased LA at the submaximal running speed compared to SHAM 21) .…”
Section: Physiological Responses At Submaximal Work Loadmentioning
confidence: 88%
“…Bailey et al (2012a) found that IPC improved 5 km treadmill running time 21) . Meanwhile, Tocco et al (2015) reported that 5000 m selfpaced running test results on an outdoor track were not improved 22) .…”
Section: Sprint (Cycle) Performancementioning
confidence: 99%
See 3 more Smart Citations